Spirituality, Religion, Social Justice Orientation, and the Career Aspirations of Young Adults. - Chenot, David; Kim, Hansung (Journal of Social Work Education)
Spirituality and religion predicted the development of social justice orientation (SJO) among young adults in a previous study (Chenot & Kim, 2013). The current study explores the manner in which the effects of spirituality and religion on social justice orientation vary depending on the career aspirations of young adults. The longitudinal data (two waves) used for this study was gathered from 14,527 students at 136 universities in the USA. Results of structural equation modeling analyses revealed that spirituality significantly predicted projected SJO behaviors among those who aspire to join the helping professions and the SJO attitudes of those who sought to join other professions. The implications of the findings for social work and social work education are discussed.